Advancing English Proficiency: A Development of the CESDEA Model in Distance Learning - Roni La'biran (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study explores the evolution and implementation of the CESDEA model (Contraction, Stimulation, Explanation, Demonstration and Assessment.) an approach designed to enhance distance learning in English speaking. The model is meticulously crafted to address the challenges posed by remote education and aims to provide an effective platform for English language acquisition. The research delves into the theoretical foundations, design principles, and pedagogical strategies underlying CESDEA. Drawing on advancements in technology and educational psychology, the model integrates interactive tools, multimedia resources, and adaptive learning techniques to create an immersive. The study also investigates the impact of the CESDEA model on student performance, motivation, and overall learning experience. Through a comprehensive analysis of data collected from participants, the research seeks to contribute valuable insights into the efficacy of the CESDEA model in fostering English proficiency in a distance learning context. The findings of this study have implications for the broader field of education and the ongoing discourse on innovative approaches to language learning in digital learning.  The noteworthy shift from a pre-test score of 54 to 84.76 signifies a substantial enhancement in speaking skills through the application of the CESDEA model. This impressive quantitative result suggests that the model effectively contributes to the development of English-speaking proficiency. The substantial increase in scores implies a positive impact on learners' linguistic abilities, highlighting the efficacy of the CESDEA model in distance learning. Consequently, these findings underscore the potential of incorporating the CESDEA model into language education programs, emphasizing its role in fostering meaningful improvements in English speaking proficiency.